2022
DOI: 10.3390/nu14142895
|View full text |Cite
|
Sign up to set email alerts
|

Alteration in Gut Microbiota Associated with Zinc Deficiency in School-Age Children

Abstract: Zinc deficiency could lead to a dynamic variation in gut microbial composition and function in animals. However, how zinc deficiency affects the gut microbiome in school-age children remains unclear. The purpose of this study was to profile the dynamic shifts in the gut microbiome of school-age children with zinc deficiency, and to determine whether such shifts are associated with dietary intake. A dietary survey, anthropometric measurements, and serum tests were performed on 177 school-age children, and 67 ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 94 publications
0
13
0
Order By: Relevance
“…Zinc is an essential micronutrient obtained from diet. About 17% of the world's human population suffers from zinc de ciency [9]. It is more prevalent in areas of high cereal and low animal food consumption [10].…”
Section: Discussionmentioning
confidence: 99%
“…Zinc is an essential micronutrient obtained from diet. About 17% of the world's human population suffers from zinc de ciency [9]. It is more prevalent in areas of high cereal and low animal food consumption [10].…”
Section: Discussionmentioning
confidence: 99%
“…Inadequate zinc intake may present a variety of clinical manifestations (growth retardation, rough skin, poor appetite, mental lethargy, abnormal neurosensory changes, and delayed wound healing) depending on the severity of the condition, and it may lead to zinc deficiency [ 93 ]. Zinc deficiency in children is responsible for an increase in the risk of developing gastrointestinal diseases (especially diarrhoea) [ 20 , 37 , 82 , 94 , 95 , 96 ], acute lower respiratory tract infections [ 27 , 69 , 70 , 97 , 98 , 99 ], and growth retardation [ 28 , 88 , 100 ]. The influence of zinc deficiency on gastrointestinal health derives from a variety of mechanisms, including the direct alteration of gut microbiota, decreased immunity, and impaired barrier integrity [ 37 , 81 , 101 ].…”
Section: Zincmentioning
confidence: 99%
“…The gut microbiota impacts the body’s bioavailability of micronutrients needed for growth and other essential biological activities. At the same time, the intake of micronutrients (e.g., zinc) affects the structure and function of the gut microbiota [ 19 , 20 ]. Zinc is an essential micronutrient, which can be found in a variety of food (meat, fish, eggs, and dairy products) [ 21 ], and it can impact gut bacterial survival by modulating the expression of proteins that are necessary for cell survival, such as superoxide dismutase, proteases, DNA polymerases, and ribosomal proteins [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…So, zinc deficiency has a disruptive influence on both intestinal microflora and host cells, culminating in inflammation of the intestinal wall (40). In one observational study alteration of gut microbiome were reported in school-aged children with zinc deficiency (41). leaky intestinal epithelial cells which increase permeability of the gut mucosal are made transferring lipopolysaccharide (LPS) into systemic circulation resulting IR and hyperinsulinemia following activation of the Toll-like receptor (TLR) 4 and 2 and LPS receptor CD14 as well as immune system (42).…”
Section: Role Of Zinc On Gut Microbiome Insulin Resistance and Hepati...mentioning
confidence: 99%